The Cassini-Huygens Mission 2003
DOI: 10.1007/978-94-017-3251-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Saturn’s Rings: Pre-Cassini Status and Mission Goals

Abstract: Abstract. Theoretical and observational progress in studies of Saturn's ring system since the mid1980s is reviewed, focussing on advances in configuration and dynamics, composition and size distribution, dust and meteoroids, interactions of the rings with the planet and the magnetosphere, and relationships between the rings and various satellites. The Cassini instrument suite of greatest relevance to ring studies is also summarized, emphasizing how the individual instruments might work together to solve outsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 201 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…Cuzzi et al (2002) provide a more detailed discussion of Saturn's rings and of the integrated ring measurements planned with the Cassini orbiter instruments. With these new capabilities, CIRS can address many of the ring objectives of the Cassini mission, particularly those pertaining to composition, ring particle thermal properties, vertical dynamics, rotation states, and radial thermal structure.…”
Section: Saturn's Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuzzi et al (2002) provide a more detailed discussion of Saturn's rings and of the integrated ring measurements planned with the Cassini orbiter instruments. With these new capabilities, CIRS can address many of the ring objectives of the Cassini mission, particularly those pertaining to composition, ring particle thermal properties, vertical dynamics, rotation states, and radial thermal structure.…”
Section: Saturn's Ringsmentioning
confidence: 99%
“…Locally this may be caused by waves excited by outer satellites. Cuzzi et al (2002) use HST observations to show that vertical structure may vary with location and the multilayer structure may not always be applicable. The A and B rings may thus be many-particles thick, whereas the thin C ring appears to be a monolayer.…”
Section: Ring Vertical Dynamics and Particle Spinsmentioning
confidence: 99%
“…More specific reviews are available for each ring system, see for instance Cuzzi et al (1984) and Esposito et al (1984) for Saturn's rings, Burns et al (2004) for Jupiter's rings, Smith et al (1986), Esposito et al (1991) and French et al (1991) for Uranus ' rings, and Smith et al (1989) and Porco et al (1995) for Neptune's rings. Finally, general reviews on rings oriented toward the Cassini mission can be found in Cuzzi et al (2002) and Esposito (2002).…”
Section: Rings Around Giant Planetsmentioning
confidence: 99%
“…More specific reviews are available for each ring system, see for instance Cuzzi et al (1984) and Esposito et al (1984) for Saturn's rings, Burns et al (2004) for Jupiter's rings, Smith et al (1986), Esposito et al (1991) and French et al (1991) for Uranus ' rings, and Smith et al (1989) and Porco et al (1995) for Neptune's rings. Finally, general reviews on rings oriented toward the Cassini mission can be found in Cuzzi et al (2002) and Esposito (2002).…”
Section: Rings Around Giant Planetsmentioning
confidence: 99%